2022
DOI: 10.3390/coatings12020189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrafast Broadband Nonlinear Optical Responses by Doping Silver into Ti3C2 Nanosheets at Visible Spectra

Abstract: Ti3C2 nanosheet is a newly discovered two-dimensional (2D) clan. It turns out to have encouraging applications for electromagnetic shielding and energy storage. Here, Ag@ Ti3C2 hybrids are precisely synthesized by using the one-step solution processing method. Also, their ultrafast broadband nonlinear optical responses in the visible region are studied systematically through nanosecond open-aperture Z-scan and transient absorption techniques. The mechanism of two-photon absorption (TPA) is disclosed in the vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…However, the diffraction peaks of Ti 3 C 2 T x are shifted to a relatively lower position than the standard peaks. For example, the peak at 7.2° (an interplanar spacing of 12.26 Å) is assigned to the (002) planes of Ti 3 C 2 T x , , which is lower than that of Ti 3 AlC 2 (9.4° for (002) planes), indicating the expansion of interlayer distance after etching with HCl/KF according to the Bragg equation (2 d sin θ = n λ, n = 1,2···). Also, the characteristic peak at 39° of Ti 3 AlC 2 disappears, implying the complete removal of the Al element in Ti 3 C 2 T x . ,, As for Ga 2 O 3 –5Ti 3 C 2 T x , the diffraction peaks of Ga 2 O 3 can be seen, and the diffraction peaks at 7.1 and 28.2° can also be indexed to the (002) and (006) planes of Ti 3 C 2 T x .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diffraction peaks of Ti 3 C 2 T x are shifted to a relatively lower position than the standard peaks. For example, the peak at 7.2° (an interplanar spacing of 12.26 Å) is assigned to the (002) planes of Ti 3 C 2 T x , , which is lower than that of Ti 3 AlC 2 (9.4° for (002) planes), indicating the expansion of interlayer distance after etching with HCl/KF according to the Bragg equation (2 d sin θ = n λ, n = 1,2···). Also, the characteristic peak at 39° of Ti 3 AlC 2 disappears, implying the complete removal of the Al element in Ti 3 C 2 T x . ,, As for Ga 2 O 3 –5Ti 3 C 2 T x , the diffraction peaks of Ga 2 O 3 can be seen, and the diffraction peaks at 7.1 and 28.2° can also be indexed to the (002) and (006) planes of Ti 3 C 2 T x .…”
Section: Resultsmentioning
confidence: 99%
“…29 However, the diffraction peaks of Ti 3 C 2 T x are shifted to a relatively lower position than the standard peaks. For example, the peak at 7.2°(an interplanar spacing of 12.26 Å) is assigned to the (002) planes of Ti 3 C 2 T x, 30,31 which is lower than that of Ti 3 AlC 2 (9.4°for (002) planes), 32 indicating the expansion of interlayer distance after etching with HCl/KF 31 The recombination condition of photogenerated electrons and holes is estimated by the PL emission spectra at 254, 280, 300, 330, and 365 nm (Figures 5b and S4) using a mixed solution of deionized water and triethanolamine (v/v = 3:1) as the dispersion solvent. The lower the intensity of the PL curve, the longer the lifetime of the photogenerated electrons.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a number of metal nanoparticles and semiconductors have been found to exhibit excellent OL responses to nanosecond laser pulses . Similarly, carbon nanomaterials such as carbon black suspensions and carbon nanotubes have been used for OL materials and other NLO applications. However, studies on the OL properties of the MXene family are fewer and mainly focused on the visible to SWIR wavelengths, and there are no reports on the OL properties of 2D Nb 4 AlC 3 and 2D Nb 4 C 3 too, as far as we know.…”
Section: Introductionmentioning
confidence: 99%
“…31 In addition, Ti 3 C 2 has been studied in the fields of photocatalysis, 32 energy conversion and storage, 33,34 biomedical, 35 and nonlinear optics. 36,37 In 2020, Wang et al investigated the broadband nonlinear optical response of Nb 2 C in the wavelength range of 400−1600 nm. The results showed that Nb 2 C exhibits saturable absorption (SA) properties in the UV band and TPA properties in the SWIR band.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation